1987
DOI: 10.1088/0268-1242/2/12/010
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of amorphous semiconductor selenium and its alloys: I. Monolayers

Abstract: Various monolayer a-Se-based photoreceptor devices were fabricated by vacuum evaporation and their electrical properties were investigated. Three experimental techniques, namely xerographic time of flight (XTOF), electroded time of flight (TOF) and xerographic discharge were used to determine the drift mobility, carrier lifetime, dark decay and residual voltage. Where possible, these measurements were carried out as a function of applied field and composition, namely As-0.3 wt%, Te up to 17 wt% and Cl up to 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…The electron mobility exhibits a slight power-law field dependence of the type µ e ∝ F n , where n was experimentally determined to be n ≈ 0.1, which is quite small. A similar µ ∝ F n type of behaviour has also been reported for other a-Se alloys (Juhasz and Vaezi-Nejad 1985, Pai 1974, Vaezi-Nejad and Juhasz 1987a. A systematic study of the field dependence of µ e will be reported separately.…”
Section: Charge-transport Parameterssupporting
confidence: 75%
“…The electron mobility exhibits a slight power-law field dependence of the type µ e ∝ F n , where n was experimentally determined to be n ≈ 0.1, which is quite small. A similar µ ∝ F n type of behaviour has also been reported for other a-Se alloys (Juhasz and Vaezi-Nejad 1985, Pai 1974, Vaezi-Nejad and Juhasz 1987a. A systematic study of the field dependence of µ e will be reported separately.…”
Section: Charge-transport Parameterssupporting
confidence: 75%
“…previous publication [5]. Results of xerographic dis-However, as described in a previous paper [ 5 ] , increase charge measurements on double layers have already in Te leads to higher thermal carrier generation and been described by one of the authors [ 6 ] .…”
Section: Introductionmentioning
confidence: 71%
“…previous publication [5]. Results of xerographic dis-However, as described in a previous paper [ 5 ] , increase charge measurements on double layers have already in Te leads to higher thermal carrier generation and been described by one of the authors [ 6 ] . The purpose results in higher dark discharge and less stable electrical of this paper is firstly to discuss the preparation and properties.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…[61,62] It is thus difficult for Te thin film to form an effective p-n junction with another highly n-doped partner. Se has a wide bandgap (E g ) of −1.8 eV, [63][64][65] enabling to increase the bandgap of Te x Se 1-x alloy and decrease the hole density (Table S1, Supporting Information). According to the relationship between E g and x, Te 0.7 Se 0.3 is selected because it has a suitable bandgap of 0.74 eV for an infrared photodetector.…”
Section: Thermodynamic Properties Of Te and Te07se03mentioning
confidence: 99%